Religion and Life - Watton, Victor W. (London : Hodder Education, 2009)
A fifth edition of this best-selling title, completely revised meet the structure, content and assessment requirements of the 2009 Edexcel Religious Studies GCSE, Unit 1.
Cover; Book title; Contents; Introduction; Section 1 Believing in God; Section 2 Matters of life and death; Section 3 Marriage and the family; Section 4 Religion and community cohesion; Glossary; Index.
Description based on print version record.
Keywords: Religion; Religion; Religions; RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Electronic books